2013
DOI: 10.1186/1471-2474-14-169
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of knee flexion characteristics and how they alter with the onset of knee osteoarthritis: a case control study

Abstract: BackgroundThe purpose of this study was to examine the differences in gait profile between patients with knee osteoarthritis (OA) and healthy control and to create motion characteristics that will differentiate between them.MethodsTwenty three patients diagnosed with knee OA and 21 healthy matched controls underwent a gait test using a sensor system (gaitWALK). Gait parameters evaluated were: stride duration, knee flexion range of motion (ROM) in swing and stance. T-Test was used to evaluate significant differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
52
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 28 publications
7
52
1
Order By: Relevance
“…A positive association is also present between KOOS and ground reaction force impulse during the first and second halves of the stance phase. The presence of an association between greater force and less pain and symptoms is congruent with prior findings that the experience of pain has the capacity to influence an individual's gait [17]. This could suggest that gait alterations after ACL reconstruction are not caused exclusively by biomechanical factors, but also by the patient's psychological experience of pain.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A positive association is also present between KOOS and ground reaction force impulse during the first and second halves of the stance phase. The presence of an association between greater force and less pain and symptoms is congruent with prior findings that the experience of pain has the capacity to influence an individual's gait [17]. This could suggest that gait alterations after ACL reconstruction are not caused exclusively by biomechanical factors, but also by the patient's psychological experience of pain.…”
Section: Discussionsupporting
confidence: 85%
“…Many studies have suggested that there are clear gait differences after ACL reconstruction, both between patients and controls and between reconstructed and contralateral knees [12‐15]. Gait variables listed in the literature as associated with the development of knee OA include increased knee adduction moment, increased medial contact force, and decreased knee flexion angles [16‐20].…”
Section: Introductionmentioning
confidence: 99%
“…The software was used to calculate the typical stride for level walking (i.e., the stride with lowest error to all other strides) (18). The following parameters were evaluated: knee ROM during swing phase, maximum knee flexion angle during the stance phase, and thigh and calf ROM during 1 gait cycle (all in degrees).…”
Section: Measuring Systemmentioning
confidence: 99%
“…Compared to healthy controls, sagittal plane ROM was significantly different in haemophilia patients with confirmed lower limb arthropathy. In patients with solitary knee arthropathy, variables previously reported as discriminative of knee osteoarthritis were affected, thus indicating that sensor-based gait analysis is able to detect joint-specific arthropathy [4,7].…”
mentioning
confidence: 87%
“…Pressure sensitive mats [2] can be used but still require a gait laboratory and do not give information on joint range of motion (ROM) and causes of altered performance, only temporal data [5]. A portable, sensor-based device was developed (GaitSmart TM ) that has proven its applicability, accuracy and reproducibility in measuring joint and limb-segment ROM in an ageing population [6] and in knee osteoarthritis [7] without the need of an optical gait lab. If such a sensor-based device provides information on gait as reflection of joint function, it can be of great importance in daily haemophilia care.…”
mentioning
confidence: 99%